NISBAH KELAMIN DAN NILAI KEMONTOKAN IKAN TABINGAL (Puntioplites bulu Blkr) DARI SUNGAI SIAK, RIAU - Pulungan, Chaidir P. (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
Tabingal fish (Puntioplites bulu Blkr) is a type of freshwater fish that commonly inhabit the Siak River, Riau. To understand the sex ratio and condition factor of this fish, a study has been conducted in April to October 2009. Total number of fish collected was 131. The sex ratio of this fish during the research period was almost constant (1:1), but the number of male was slightly higher than that of the female. Most of fish collected were 87-241 mm TL and they are categorized as undeveloped gonad fish. The factor condition was ranged from 1.21-1.50.